MATCHING AND STITCHING FOR SURFACE IDENTIFICATION - Jamari, Jamari (ROTASI, 2006)
An algorithm to determine changes in surface topography on asperity level has been developed in this paper. The software tool stitches small but detailed images together to create one large image. If such an image is made before and after an experiment, their difference shows a direct 3D view of the changes in micro-geometry, rather than a change in surface parameters such as RMS or CLA roughness. The algorithm is described in detail and demonstrated by appling to real rough surfaces.